Economics, demand and challenges of mechanization: A data note on mechanization service provision in Bangladesh - Aravindakshan, Sreejith; Parupalli, Bharathi; Uddin, Kafil; Hoque, Muhammad Arshadul; Islam, Saiful; Calvert, Owen; Krupnik, Timothy J. (TAFSSA, 2024)
This note presents data from two surveys (Phase 1 & 2) conducted between December 2023 and February 2024. It assesses the operational status and experiences of 2,608 Machinery Service Providers (MSPs) across 21 districts in Bangladesh. The first phase included MSPs with less than a year to over two years of experience in both coastal and non-coastal agroecosystems. It captured data on the perceived future demand for agricultural machinery and the challenges faced in service provision.. The second phase involved a focused survey of MSPs and farmers to gather insights on the economic benefits and costs of mechanization versus manual labor. This dataset establishes a baseline for understanding the current state of mechanization and informs future studies on scaling mechanization and developmental interventions.